The Effect of Meridional and Overall Aniseikonic Corrections on Perceived Distortion Due to Small Astigmatic Correction:: Bitoric Spectacle Lenses - Robertson, K.M; Remole, A (Canadian Journal of Optometry, 2021)
A 35 year old male had been periodically prescribed a complete correction for his small amounts of astigmatic hyperopia. Compliance was unsuccessful due to the apparent tilting of the patient's visual surroundings. Using measurements obtained on a new eikonometer called the Multimeridional Apparent Frontoparallel Plane, bitoric lenses were prescribed and supplied. Aniseikonia and visual perception was evaluated with meridional aniseikonia corrected and then with meridional and overall aniseikonia corrected. Only the latter gave the patient full satisfaction.